MINIMALLY INVASIVE CIRCUMFERENTIAL ARTHRODESIS OF THE FOURTH LUMBAR LEVEL FOR SPONDYLOLISTHESIS TREATMENT - Oviedo,Jose Enrique Salcedo (2018)
ABSTRACT Objective: To know the clinical and radiographic results of patients with L4-L5 degenerative spondylolisthesis grade I, II, and III surgically treated with minimally invasive 360-degree arthrodesis. To determine the clinical and radiographic results according to the Oswestry Index 6 months after surgery and the percentage of postsurgical reduction in these patients. Methods: The present study was developed in the Department of Spinal Surgery of the Unidad Médica de Alta Especialidad Lomas Verdes, from October 2016 to August 2017. It is a prospective, cross-sectional, comparative observational study. We evaluated the reduction of the listhesis using pre and post-operative radiographs, as well as the Oswestry Disability Index. Results: The sample was composed of 12 patients, eight females and four males, showing a statistical significance in the Student’s t test, with p=0.05 for both variables. Conclusions: Degenerative spondylolisthesis of the 4th lumbar level is a very frequent pathology that affects groups of productive age and represents a burden not only for the patient, but also for the community. This surgical technique showed a high level of security and confidence for its resolution, showing results comparable to the literature. However, it requires certain technical resources and training to be performed. Evidence Level II; Prospective comparative study.